2008
DOI: 10.1200/jco.2007.11.5980
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Randomized Controlled Trial of an Epidermal Growth Factor Vaccine in Advanced Non–Small-Cell Lung Cancer

Abstract: Vaccination with EGF was safe and provoked an increase in anti-EGF antibody titers and a decrease in serum EGF. There was a direct correlation between antibody response and survival. There was a direct correlation between decrease in serum EGF and survival. In patients younger than 60 years, vaccination was associated with increased survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
128
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(135 citation statements)
references
References 20 publications
(4 reference statements)
3
128
0
4
Order By: Relevance
“…In this small trial conducted by Neninger et al, patients were randomized to receive either vaccination plus BSC or BSC alone. The investigational vaccine was administered on days 1, 7, 14, 28 and monthly thereafter after administration of a priming dose of cyclophosphamide (200 mg/m 2 ) [57]. The measurement of EGF in patients' serum showed reduced EGF concentrations in those in the experimental arm, which indirectly confirmed that CIMAVax induced production of anti-EGF antibodies.…”
Section: Muc1 and L-blp25 (Tecemotide)mentioning
confidence: 84%
See 1 more Smart Citation
“…In this small trial conducted by Neninger et al, patients were randomized to receive either vaccination plus BSC or BSC alone. The investigational vaccine was administered on days 1, 7, 14, 28 and monthly thereafter after administration of a priming dose of cyclophosphamide (200 mg/m 2 ) [57]. The measurement of EGF in patients' serum showed reduced EGF concentrations in those in the experimental arm, which indirectly confirmed that CIMAVax induced production of anti-EGF antibodies.…”
Section: Muc1 and L-blp25 (Tecemotide)mentioning
confidence: 84%
“…In addition, a statistically significant improvement in survival (11.7 vs 3.6 months; p = 0.002) was also seen for patients with EGF antibody titers ‡ 1:4000. No critical side effects occurred in this trial [57]. A larger Phase II/III (Malaysian trial) study was started but interrupted in 2011 due to poor enrollment [58].…”
Section: Muc1 and L-blp25 (Tecemotide)mentioning
confidence: 99%
“…This vaccine is cytostatic and prevents EGF binding to its receptor through development of antibody-mediated immunity to EGF. In a randomized phase II study, patients with advanced NSCLC who received the EGF vaccine after first-line chemotherapy had a trend toward improved survival (6.5 m vs. 5.3 m, P ¼ 0.098); however this was not statistically significant (43). Subsequently, enrollment has been completed on a phase III study in the same disease setting with results awaited (30).…”
Section: Egfmentioning
confidence: 99%
“…In a phase II study, 80 patients with stage IIIB or IV NSCLC were randomized to receive EGF vaccination or BSC [100]. As with L-BLP25, vaccination was primed with cyclophosphamide and the EGF vaccine given on days 1, 7, 14, and 28, and monthly thereafter.…”
Section: Clinical Experience With Antigen-independent Immunomodulatormentioning
confidence: 99%